Dealing with the complexity of conjugated and self‐assembled polymer‐nanostructures using field‐flow fractionation. Issue 3 (5th March 2021) - Muza, Upenyu L.; Boye, Susanne; Lederer, Albena
Abstract: Broad diversity and heterogeneity are inherently showcased by both natural and synthetic macromolecular structures. The high application potential for such structures and their combinations calls for novel analytical approaches that allow for comprehensive characterization and a full understanding of their complex composition. This review gives an overview of recent advances in designing and fabricating bioconjugated and self‐assembled polymer structures, and introduces adequate characterization protocols for sufficient elucidation of their specific molecular properties. Possible pitfalls in their analysis are demonstrated, and potential alternatives are discussed. The primary focus is on addressing the highlights, and future prospects of applying field‐flow fractionation coupled and/or hyphenated to different detection methods as a powerful separation and analytical technique for bioconjugate and self‐assembled nanostructures.